Sintesis dan Uji Aktivitas Antibakteri N,N'-Divanilidenaetilendiamina - Hayun, Hayun; Munim, Abdul; Hariria, Dini; Aunillah, Ulfah (Majalah Ilmu Kefarmasian, 2007)
The study of synthesis and antibacterial activity test of N,N'-divanilidene-ethylendiamine was performed. N,N'-divanilidene-ethylendiamine was synthesized by reacting vaniline with ethylendiamine in ethanol pH 1, and the structure was elucidated based on IR and 1H-NMR spectra data. Antibacterial activity test was performed using minimum inhibition concentration method (MIC) against Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853, and Escherichia coli ATCC 25922. The results showed that N,N'-divanilidene-ethylendiamine has antibacterial activity with MIC of 2 mg/mL against the the bacteria.